Penerapan Bisnis Proses Manajemen Dalam Kesiapan Sumber Daya Manusia Dan Sistem Operasional Dalam Rencana Pembukaan Cabang Baru Pada Rumah Makan Padang Talago Indah - Dipo Ilham Firdaus; Eka Sudarmaji (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Application of Business Management Process in Human Resource and Operational System Readiness in the Plan to Open a New Branch at Padang Talago Indah Restaurant The high level of competition in the culinary industry at the scale of micro, small, and medium enterprises (MSMEs) requires business actors to have a mature expansion strategy and supported by strong internal readiness. This research aims to analyze the readiness of human resources and operational systems through the Business Process Management (BPM) approach in supporting the expansion plan to open new branches at Padang Talago Indah Restaurant. The research method used is qualitative descriptive by conducting in-depth interviews and business process documentation of key informants including business owners, operational managers, and employees in the 2026 research period. The results of the study show that the level of readiness of human resources still faces obstacles due to limited work experience (60% of employees have a working period of less than one year), lack of formal technical skills, and weak structured division of tasks. From the operational aspect, the current workflow mapping (As-Is) detects serious bottlenecks in the process of procuring daily fresh raw materials and the absence of standard standardization, thus triggering variability in food taste and service quality between shifts. Through the design of a new proposed model (To-Be), this study succeeded in formulating an integrated operational standardization and periodic competency training program. The conclusion of this study confirms that the success of opening new branches is highly dependent on the transformation of conventional business models towards a standardized operational process governance system to ensure consistent replication of business quality in new locations.